2020
DOI: 10.1167/iovs.61.3.40
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Structure inGNAT2-Associated Achromatopsia

Abstract: The purpose of this study was to report GNAT2-associated achromatopsia (GNAT2-ACHM) natural history, characterize photoreceptor mosaic, and determine a therapeutic window for potential intervention. METHODS. Patients with GNAT2-ACHM were recruited from a single tertiary referral eye center (Moorfields Eye Hospital, London, UK). We performed longitudinal clinical evaluation and ophthalmic examination, and multimodal retinal imaging, including adaptive optics scanning light ophthalmoscopy, quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“… 15 , 16 In CNGA3 and CNGB3 genotypes, variable degrees of ellipsoid zone (EZ) disruption and residual cone structure have been observed. 16 20 GNAT2 -ACHM typically presents with a continuous EZ, 21 , 22 in contrast to PDE6C -ACHM and ATF6 -ACHM, for which most of the patients have no residual foveal cones. 11 , 23 Evidence of structural changes over time has been suggested by some studies 24 , 25 but not others.…”
mentioning
confidence: 99%
“… 15 , 16 In CNGA3 and CNGB3 genotypes, variable degrees of ellipsoid zone (EZ) disruption and residual cone structure have been observed. 16 20 GNAT2 -ACHM typically presents with a continuous EZ, 21 , 22 in contrast to PDE6C -ACHM and ATF6 -ACHM, for which most of the patients have no residual foveal cones. 11 , 23 Evidence of structural changes over time has been suggested by some studies 24 , 25 but not others.…”
mentioning
confidence: 99%
“…[21][22][23][24] Marked variability in the cone mosaic has been observed across patients with ACHM. 23,[25][26][27][28] Nonconfocal split-detection AOSLO demonstrated that inner segment structure remained in these "dark spaces." The degree of remnant inner segment structure may be important for participant selection for gene therapy trials and could be used to identify patients most likely to benefit from cone-directed rescue.…”
Section: Introductionmentioning
confidence: 99%
“… 21 24 Marked variability in the cone mosaic has been observed across patients with ACHM. 23 , 25 28 Nonconfocal split-detection AOSLO demonstrated that inner segment structure remained in these “dark spaces.” The degree of remnant inner segment structure may be important for participant selection for gene therapy trials and could be used to identify patients most likely to benefit from cone-directed rescue. Peak foveal cone density is a widely used metric, both as an anchor for locating other regions of interest and as a statistic in its own right; however, there have been relatively few studies examining the repeatability of these measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, only individuals with CNGA3 or CNGB3 genotypes were included. While there are reported differences in cone structure in the GNAT2, 59,60 ATF6, 61 and PDE6C forms of ACHM, 62 it is unknown whether a FAZ is present in individuals with ACHM caused by these genotypes. Additionally, there are reports of residual cone function in patients with ACHM, 63 and patients with GNAT2-associated ACHM have been reported to have cone-mediated visual function at high radiances (although only at low temporal frequencies).…”
Section: Discussionmentioning
confidence: 99%